AUDIT SISTEM INFORMASI APLIKASI MY BEST DI UNIVERSITAS BINA SARANA INFORMATIKA MENGGUNAKAN COBIT 5 - Arif Rahman, Muhammad Syafickri Rhamzani, Wahyu Ningrat, Riza Fahlapi (ADISAM PUBLISHER, 2024)
Information system audit is a critical activity to ensure that the information system operates according to the organization's needs, meets security standards, and minimizes the risk of failure or violations. COBIT 5 (Control Objectives for Information and Related Technologies) is a relevant framework for auditing the